2004
DOI: 10.1002/jnr.20314
|View full text |Cite
|
Sign up to set email alerts
|

Ageing‐related decline in adenosine A1 receptor binding in the rat brain: An autoradiographic study

Abstract: The adenosine system has important neuromodulatory and neuroprotective functions in the brain. Several lines of evidence suggest that ageing is associated with major alterations in the adenosine system, which may be partially responsible for changes in sleep, mood, and cognition. In the present study, we examined adenosine A1 receptor density in the rat brain by means of quantitative autoradiography to obtain a detailed anatomical overview of the changes during ageing. A1 receptor binding was assessed in young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…An imbalance in adenosine receptors has been observed in multiple conditions, 21 particularly with progressive aging, 18,19 which has consequences to their modulatory effects. 19,41 In the aged rat brain, adenosine A 1 receptor density is decreased, 47 particularly in hippocampus and cortex. 18 However, A 2A receptor levels are differently affected: they decrease in striatum, but in contrast there is an increase in their expression in cortical and hippocampal areas.…”
Section: Discussionmentioning
confidence: 99%
“…An imbalance in adenosine receptors has been observed in multiple conditions, 21 particularly with progressive aging, 18,19 which has consequences to their modulatory effects. 19,41 In the aged rat brain, adenosine A 1 receptor density is decreased, 47 particularly in hippocampus and cortex. 18 However, A 2A receptor levels are differently affected: they decrease in striatum, but in contrast there is an increase in their expression in cortical and hippocampal areas.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the old rats failed to exhibit those changes associated with homeostatic rebound from sleep loss (increased delta, increased NR and increased sleep consolidation) may simply be because the sleep loss incurred by ICV Hcrt-1 in old rats was of insufficient magnitude to induce a homeostatic response. Nonetheless, previous studies have demonstrated that other known neurobiological mediators of homeostatic sleep regulation, including adenosine [Meerlo, et al, 2004; Murillo-Rodriguez, et al, 2004], are disrupted with age in Wistar rats.…”
Section: Discussionmentioning
confidence: 99%
“…Given the more superficial sleep in old rats and the suggested role for adenosine in promoting SWS/SWA, these data indicated that the sensitivity of adenosine receptors declines with increasing age. In support of this hypothesis, autoradiography in rat brain slices and PET with 18 F-CPFPX in humans showed that adenosine A 1 receptor binding was significantly reduced with age in many cortical and subcortical brain regions (Meerlo et al, 2004; Meyer et al, 2007). No such studies were performed to date to investigate age-related changes in functional aspects of A 2A receptors in the brain.…”
Section: Advanced Age Alters Functional Aspects Of the Adenosinergic mentioning
confidence: 91%